Финансиската доларизација, либерализацијата на капиталните текови и финансиската стабилност - Јовановски, Кирил (Економски факултет, УКИМ, Скопје, 2014)
This paper gives different perspective form the standard model of financial turbulences. In that model the key factor for generating the crisis in terms of fixed exchange rate was the fiscal inconsistency. Such perspective is different form the dominant literature also. The literature concerning the financial crises describes them as a consequence of weak supervision of the banking sector and its underdevelopment. Main interest of the paper is the appearance, development and the risks financial dollarization is generating. Therefore detecting the determinants and risks from the financial dollarization should show that this phenomenon is not a fertile as one usually thinks. The paper analyzes all benefits that may occur from the official and partial dollarization of the economy. In addition a perspective for selected countries that has faced severe financial crises due to foreign currency loans is presented. There are two main thesis that are tested in this paper. First, is there any new way of dealing with the high level of deposit dollarization? In that term, the paper seeks for different signal that the major economic policies should send to the agents in the economy. Second, which are the determinants of the foreign currency loans in the countries of South East Europe? Is there any linkage between the time inconsistency of the macroeconomic decisions and the financial dollarization? Testing the precious thesis, this paper concludes that the major factor for high deposit dollarization in Macedonia if the fear of floating and the level of inflation. Similar to these conclusions, the main factors for appearance of the credit dollarization in the countries of South East Europe are changes in the nominal and real exchange rate, openness of the economy and capital markets development.
Financial dollarization, capital flows liberalization and financial stability
Докторска дисертација одбранета во 2014 година на Економскиот факултет во Скопје, под менторство на проф. д–р Михаил Петковски.
Keywords: financial dollarization, financial instability, depreciation, financial crises episodes, dollarization determinates